Ultrastructure of the intramandibular gland of workers and queens of the stingless bee, Melipona quadrifasciata - Da Cruz-Landim, Carminda [UNESP]; Gracioli-Vitti, Luciana F. [UNESP]; Abdalla, Fábio C. (My University, 2011)
The intramandibular glands of workers and queens of Melipona quadrifasciata Lepeletier (Hymenoptera: Apidae), at different ages and from different functional groups, were studied using light and transmission electron microscopy. The results demonstrated that these glands are composed of two types of secretory structures: 1.A hypertrophied epidermis on the dorsal side of the mandible that is an epithelial gland. 2. Free secretory cells filling the inner spaces of the appendices that constitute a unicellular gland. The epithelial gland is larger in the young (1-2-day-old workers), and the gland becomes involuted during the nurse worker stage. The unicellular glands of the workers posses some secretion during all of the studied phases, but secretory activity is more intensive in the foraging workers. Vesicles of secretion are absent in the unicellular glands of queens. These results demonstrate that these glands show functional adaptations in different castes corresponding to the functions of each caste.
Keywords: Exocrine glands; Light microscopy; Morphology; Transmission electron microscopy; Workers phases